Strategi Pengembangan Dan Implementasi Sistem Pendaftaran Berbasis Web Meningkatkan Partisipasi Calon Atlet Riyan’s Taekwondo Club - Fatimah Zahira Chaniago; Roberto Kaban; Dewi Yohana Br Ginting (Institut Teknologi dan Bisnis Indonesia, 2026)
The increase in prospective athletes' participation has become one of the main challenges in the modern sports world. To address this challenge, this study developed and implemented a web-based online registration information system aimed at simplifying the registration process and attracting more prospective athletes. This system is designed using an iterative and collaborative software development approach to ensure flexibility and responsiveness to user needs. The key features implemented in this system include online registration, automatic data verification, and real-time registration status notifications. The evaluation of this system showed a significant increase in the number of registrants, as well as improved user satisfaction due to better ease of use and accessibility. The results of this study provide a significant contribution to the technology development strategy in the sports field, with the potential for wider application.